Jawabanmu

Jawaban paling cerdas!
2014-03-02T12:14:52+07:00
.........................................................................................................................
1 5 1
2014-03-02T12:29:45+07:00
F(x) = x-2 = 11
f(x) = x+1 = -4 
f(x) = x2-x-2 sisa .. ?

caranya gunakan pemisalan S (x) = aX+b
X-2 = 0   x+1 = 0
X=2        x= -1
substitusikan
f(x) = x-2 
f(2) = 2a+b = 11
f(-1) = -a+b = -4 -
          3a   = 15
             a = 15
                    3
              a= 5
eliminasikan
2a+b = 11
2(5)+b=11
10+b=11
b = 11-10 = 1

karena S(X) dimisalkan aX+b
maka s(x) = 5x+1

selesai deh :)